Spatial Property: World Approaches and the National Law of Ukraine - Mytsa, Yurii (Teisė, 2022)
The article considers the analysis of construction of spatial (floor) property, which assumes the existence of real property rights to individual premises in buildings in relation to such rights with the right to the building as a whole.
Keywords: property; real estate; rights to premises; apartment house; apartments; premises; floor property; spatial property